Real time wireless monitoring and controlling of 3-D single point incremental tool - Hatam, Huda; Abdul Aziz, Faieza; Wan Hasan, Wan Zuha; Mohd Ariffin, Mohd Khairol Anuar (American Scientific Publishers, 2017)
Maintenance of machine tools can be improved significantly by analyzing the operating of manufacturing process with the real-time monitoring system for 3-D single point deformation measurements. Therefore, the process of manufacturing could be optimized with less cost. Recently, wireless technology and internet of things (IOT) applied on intelligent machine has witnessed a significant advance with augmented virtuality, the analysis and the process certainly would contribute to enhance the intelligence of that machine. This paper presents a group of the wireless sensors and 3D animation technologies for data monitoring and analyzing. Three degree of freedom robotic hand structure has been selected as a prototype to be form the process of the Single Point Incremental Forming (SPIF). The inverse kinematics problem of the conversion method for the position and orientation of a robot manipulator has been addressed to transfer from Cartesian space to joint space. Algebraic and inverse kinematic solutions have been adopted to analyze the rotation, compound rotations and inverse rotations. Graphical User Interface (GUI) in MATLAB environment has been reported with the kinematic structure of a serial-link manipulator by using the Denavit-Hartenberg parameters and a homogeneous transform matrix in toolbox software based on mathematical modeling equations for the moving parts of the selected 3D robotic hand. Investigated the synchronization of real time of the moving axes data with the same monitored animated robot and the results was accurate representation and interpretation of the actual moving of the prototype (robot hand). Real robot hand and animated robot which it designed in Robotics Toolbox in MATLAB are similar in design and orientations of axes, but it differs in the time spent for every movement. It is found that this monitoring and controlling can be achieved with using XBee Pro S1 capability as a wireless nodes with its built in microcontroller and suitable feedback sensors with minimum power consumption and less cost.